(untitled) (Research, Society and Development, 2025)
The immune system operates through multiple mechanisms, not only to protect against foreign agents but also to combat neoplasms and graft rejection. Additionally, it employs selective self-tolerance mechanisms to prevent attacks on the body’s own antigens. Dysregulation of these mechanisms, which can result from genetic alterations and/or the activity of infection-causing agents, culminates in the development of autoimmune diseases (AD). Genetic defects, such as changes in the genes responsible for the major histocompatibility complex (MHC) and polymorphisms, may contribute to the etiology of these diseases. Furthermore, bacteria and viruses can influence the pathophysiology of these diseases by inducing intense inflammation that leads to endothelial damage or stimulates the expression of autoantibodies, as observed during SARS-CoV-2 infection. Specifically, the virus responsible for Covid-19 may exacerbate the prognosis of patients with pre-existing autoimmune diseases and contribute to their chronicity. In this context, the aim of this study is to conduct a systematic literature review on genetic factors and the role of infections in the development of autoimmune diseases.